Lie Group Analysis of a Flow with Contaminant-Modified Viscosity - Raseelo J. Moitsheki (Journal of Applied Mathematics)
A class of coupled system of diffusion equations is considered. Lie group techniques resulted in a rich array of admitted point symmetries for special cases of the source term. We also employ potential symmetry methods for chosen cases of concentration and a zero source term. Some invariant solutions are constructed using both classical Lie point and potential symmetries.